ANALISIS MELODI LAGU ANEUK YATIM CIPTAAN RAFLY KANDE - Rozak, Abdul; Pratama, Haria Nanda; Gusmanto, Rico (UNIVERSITAS INDO GLOBAL MANDIRI)
Aneuk Yatim is a song created in 1999 by Rafly, has a message and meaning of peace in responding to issues of political upheaval in Aceh, and represents the condition of children in Aceh during the conflict. Through lyrics and melody, Rafly is able to create an atmosphere of sadness that can be felt by the community regarding the conditions and situations during the conflict. The vocals in the song Aneuk Yatim, written by Rafly, have a melodic structure and form consisting of musical ornaments, melodic travel arrangements and scales. This study describes the melody in the song Aneuk Yatim written by Rafly Kande using Western music theory. The purpose of this study is to determine the melody analysis method of pop music in Indonesia in general and regional pop music in particular. The approach taken is a qualitative approach, with descriptive analysis methods, assisted by ethical and emic approaches to facilitate the smoothness of the data search process. The selection of methods and approaches is carried out through documentation, observation, and interviews with participants. The form and structure of the melody in the song Aneuk Yatim, written by Rafly Kande, consists of two parts with a tempo of 60 bpm, each of which is divided into two sentences / periods. The sentences are arranged based on various forms of motifs, each of which has a melody and scale that is repeated in the next period / sentence with a slight change in the melody at the end of the figures (closing phrase). The scale used in this song is the Original Minor and Harmonious Minor, with sequences development techniques, diminished, and augmented. The results of this study are expected to become a reference and reference in the perspective of formal objects and material objects, related to the analysis of the form and structure of the melody, the development of melodic patterns discussed in Western music theory.